AUTECOLOGY AND DISTRIBUTION PATTERN OF BACCAUREA MACROCARPA IN SOUTH KALIMANTAN OF INDONESIA - Gunawan; Anafarida O.; Mahmudah N.; Rizki M.I. (Russian Journal of Agricultural and Socio-Economic Sciences, 2021)
Baccaurea macrocarpa is an underutilized plant, which has potential as a medicinal plant. However, a little information known about this plant, especially on microhabitat and distribution pattern. This study is the first to reveal the microhabitat dan distribution pattern of B. macrocarpa in South Kalimantan. This study used purposive sampling method by exploring the area where B. macrocarpa commonly found. Distribution was analyzed used Morishita index and the microhabitat analysis was performed using Principal Component Analysis (PCA) generated from Minitab 16 software.